Improving Existing Punjabi Morphological Analyzer using N-gram - Sharma, SK (International Journal of Computer Sciences and Engineering, 2025)
Morphological analysis is an essential tool for almost all Natural Language Processes like POS tagging, Grammar checking, Sentence simplification, generation of Treebank and parsing. In this research article, author has used N-gram statistical technique to improve the existing morphological analyzer. The main factor that reduces the accuracy of morphological analyzer is presence of unknown words. In this research article author has used n-gram approach for detecting the POS tag of unknown word. The results shows an average precision of 82.34, recall 70.20 and F-measure 75.74.